La marca Perú y su incidencia en la promoción de la oferta turística de nuestro país durante el año 2017; analizando su posicionamiento y su consolidación en el mercado internacional - Luyo Almonte, Marisol del Carmen (2019)
The present research work entitled "The PERU Trademark and its Incidence in the Promotion of the Tourist Offer of Our Country during the year 2017; Analyzing its Positioning and Consolidation in the International Market". Its general objective is to determine the incidence in the promotion of the tourist offer that allowed the positioning and consolidation of the Peru brand in the international market during the year 2017, the design to be used will be descriptive. The research work is a qualitative approach. Taking as a study sample to the tourist company of the region, for the development of this work the research is collected data for the definition of variables to which will apply instruments such as the survey and the record of observation in a dichotomous scale. The reliability and validity will be subject to the results obtained. The results obtained after the procedure and the analysis of the data will give us a glimpse of the significance of the promotion of the Perú Brand offer for consolidation in the international market, as a laudable market strategy.